Antianhedonic Effect of Repeated Ketamine Infusions in Patients With Treatment Resistant Depression - Wilkowska, Alina; Wiglusz, Mariusz Stanisław; Gałuszko-Wegielnik, Maria; Włodarczyk, Adam; Cubała, Wiesław Jerzy (Frontiers in Psychiatry, 2021)
Anhedonia constitutes one of the main symptoms of depressive episode. It correlates with suicidality and significantly effects the quality of patient’s lives. Available treatments are not sufficient against this group of symptoms. Ketamine is a novel, rapid acting strategy for treatment resistant depression. Here we report the change in symptoms of anhedonia measured by Snaith-Hamilton Pleasure Scale as an effect of eight ketamine infusions as an add-on treatment in 42 patients with treatment resistant depression. We also determined the effect of this change on the severity of depressive symptoms measured by Inventory for Depression Symptomatology-Self Report 30-Item (IDS-SR 30). We have observed statistically significant decrease in the level of anhedonia during ketamine treatment. After adjusting for potential confounders we have found that significant reduction in Snaith-Hamilton Pleasure Scale (SHAPS) after each infusion and 1 week post treatment was observed only among patients who did not use benzodiazepines. The reduction in symptoms of anhedonia mediates the antidepressive effect of ketamine. The results need replication in a larger randomized placebo controlled trial.